Kebijakan dan Pemikiran Ekonomi Islam pada Masa Dinasti Umayyah - Firyal Jilan Nuha; Hikmal Azkia Muharam; Nazmi Ibnu Shina Zein; Lina Marlina (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2025)
This study explores the development of Islamic economic thought during the Umayyad Dynasty (661-750 CE). Using descriptive and literature review methods, this research highlights the integration of Islamic principles into economic policies and practices during this era. Key findings indicate that the Umayyad rulers implemented zakat, kharaj, and jizyah systems to ensure wealth redistribution and welfare. Infrastructure development and monetization through dinar and dirham currencies also contributed to economic stability while adhering to Islamic ethical values. Despite challenges such as social inequality and administrative inefficiencies, the Umayyad Dynasty laid a foundation for future Islamic economic systems that prioritize justice and prosperity.